Analisis Perlindungan Hukum Terhadap Pelanggaran Merek Dagang Produk Lokal di Pasar Digital - Gustina Sari; Windi Octaviani; Bonaraja Purba (Pusat Riset dan Inovasi Nasional, 2025)
The growth of the digital marketplace presents both opportunities and challenges for MSMEs (Micro, Small, and Medium Enterprises) in protecting their trademarks. This study aims to analyze the legal protections against trademark infringement of local products in the digital marketplace, identify the challenges faced by MSMEs, and formulate effective preventive and repressive strategies. The research employs a normative-empirical approach, analyzing Law No. 20 of 2016 on Trademarks, the Electronic Information and Transactions Law (ITE Law), and a case study of the MSME MoriGe. The findings reveal that while Indonesia's legal framework for trademark protection is adequate, its implementation faces obstacles such as low awareness among MSMEs regarding trademark registration, slow law enforcement, and the complexity of infringements in the digital space. This study recommends proactive trademark registration, enhanced collaboration with digital platforms, and widespread legal outreach to MSMEs. The research findings are expected to contribute to strengthening legal protections for local product trademarks in the digital era.